Concurrent sensorimotor temporal recalibration to different lags for the left and right hand - Sugano, Yoshimori; Keetels, Mirjam; Vroomen, Jean (Frontiers in Psychology, 2014)
Perception of temporal synchrony between one’s own action and the sensory feedback of that action is quite flexible. We examined whether sensorimotor temporal recalibration (TR) involves central or motor-specific components by concurrently exposing the left and right hands to different lags. The experiment was composed of a pre-test, an adaptation phase, and a post-test. During the adaptation phase, participants tapped their left and right index fingers in alternating fashion while each tap induced an auditory feedback signal (a short click sound). One hand was exposed to a long delay between the tap and the sound (~150 ms), while the other hand was exposed to a subjective no-delay (~50 ms). Before and after the adaptation phase (the pre- and post-test), participants tried to tap in synchrony with pacer tones (ISI = 1000 ms). The results showed that the hand that was exposed to the delayed sound corrected for this delay by tapping earlier (a larger anticipation error) than the no-delay hand, indicating TR. Different amounts of TR were found when the left and right hand were concurrently exposed to the same versus different delays. With different exposure- delays for the two hands, there was a TR even for the hand that did not experience any delay in the feedback signal. However, it is not the case with the same exposure delay for the two hands. TR of the hand that experienced delayed feedback also occurred faster and was more complete (~40% greater than that of the hand with no subjective delay) if the two hands were exposed to the same rather than different delays (~20% greater than that of the hand with no subjective delay). These results suggest the existence of cross-talk between the hands, where both central and motor-specific components might be involved.